Науково-історична спадщина М. Лозинського - Нагірняк, А. Я. (Lviv Polytechnic Publishing House, 2016)
Проаналізовано науково-історичну спадщину М. Лозинського про процеси, що відбувались в Україні під час національно-визвольних змагань. Вказано, що основними напрямами наукових досліджень М. Лозинського була державно-правова та міжнародно-правова проблематика. In this article Lozynskyi’s historical heritage is taken into account while analyzing processes which took place in Ukraine during national-liberation movement. The article states that M. Lozynskyi began his career in the well-known Lviv newspaper “Dilo”, where he started to work in 1900, and later become an editor of it until theWorldWar I. In the following research the works of M. Lozynskyi dedicated to national-liberation movement and its defeat are observed. The main part of his works refers to the defense of the Ukrainian people rights during the national-liberation movement and the idea of Ukrainian state is brought up. His later works related to the problems of the international rights. The following articles were written: “The Protection of National Minorities in the International Law” (1923), “The Struggle for National identiy in the Versailles Agreement” (1923), university textbook “The International law” (1922) Living in Prague he campaigned for the state rights of Ukraine. In this article is mentioned that the historianM. Lozynskyi looks into the violation of the Ukrainian people rights by Poland which occupied the main part of west Ukrainian lands. The unfair politics of the League of Nations is also highlighted. M. Lozynskyi emphasizes that the lands of the western Ukraine in any case can not be considered inhabited by a national minority,as the Ukrainian people comprise 60 % of population in each of the three provinces of Halychyna. Summarising, the works of M. Lozynskyi demonstrate the two main aspects: state legal problems of the development of Ukraine and international-legal range of problems in particular those which relate to the national minorities.
Keywords: М. Лозинський; Галичина; Польща; національно-визвольний рух; М. Lozynskyi; Galychyna; Poland; national-liberation movement; 930(477)